Evaluation of Fungicides, Phytoextracts and Germplasm Screening Against Lasiodiplodia Theobromae Causing Fruit Rot of Jackfruit (Journal of Plant Disease Sciences, 2023)
The current study was carried out to evaluate the efficacy of different fungicides against the Lasiodiplodia theobromae under laboratory conditions, which demonstrated that all of the fungicides inhibited the pathogen significantly. Carbendazim 50% WP (0.1%) and combi product Carbendazim 12% + Mancozeb 63% WP (0.15%) were the most effective fungicide which showed complete inhibition of the mycelial growth of the pathogen followed by Fludioxanil 230 SC (0.15%), Difenoconazole 25% EC (0.1%), combination fungicide Tebuconazole 50%+ Trifloxystrobin 25% WG (0.1%), Mancozeb 75% WP (0.2%) and Copper oxychloride 50% WP (0.25%), respectively over control. The mean percent inhibition of mycelial growth was recorded in adulsa leaf extract (22.03%), eucalyptus leaf extract (19.81%), tulsi leaf extract (19.08%) and garlic clove extract (18.89%) of the nine plant extracts. Among the fifteen germplasm and three varieties of jackfruit tested for resistance to fruit rot in the laboratory, the variety Konkan prolific was found to be resistant to Lasiodiplodia fruit rot disease. Two varieties/germplasm were moderately resistant to Lasiodiplodia fruit rot, while three germplasm were moderatelysusceptible.
Keywords: Jackfruit; Lasidiodiplodia theobromae; Fungicides; Screening